PENINGKATAN KEMAMPUAN BERBICARA BAHASA INGGRIS MELALUI TEKNIK MEMBACA BERITA DI SMA DEK PADANG - Edwar Kemal; Wahyudi Rahmat; Refa Lina Tiawati; Suci Dwinitia (RANGKIANG: Jurnal Pengabdian Pada Masyarakat, 2019)
Learning English, especially speaking skills, requires a variety of accurate strategies. The aim is to make it easier for students to learn English, the more ways they can learn it the easier it is to master it. However, it is important to remember that learning English is not learning knowledge that requires high logical reasoning, memorizing formulas, mastering tenses, grammar, and formal English grammar, and so on. But learning English is nothing more than a skill that is continuously practiced until it is accustomed, any language learned requires the practice of speaking the language learned.